2016
DOI: 10.3389/fvets.2016.00062
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Fermentation of Anti-Methanogenic Nitrate- and Nitro-Containing Forages In Vitro

Abstract: Nitrate, 3-nitro-1-propionic acid (NPA) and 3-nitro-1-propanol (NPOH) can accumulate in forages and be poisonous to animals if consumed in high enough amounts. These chemicals are also recognized as potent anti-methanogenic compounds, but plants naturally containing these chemicals have been studied little in this regard. Presently, we found that nitrate-, NPA-, or NPOH-containing forages effectively decreased methane production, by 35–87%, during in vitro fermentation by mixed cultures of ruminal microbes com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…The reduction in the proportion of ruminal acetate 12 h after supplementation and higher butyrate concentrations by ENS is in line with results from trials of mixed cultures of rumen microbes incubated with nitrate and nitro-compounds (Zhou et al, 2012; Mamvura et al, 2014; Anderson et al, 2016). It may be a compensatory route for the dispensing of reducing equivalents during the inhibition of rumen methanogenesis, shifting electron transfer mainly to more reduced fatty acids such as propionate and butyrate, as this subsequently results in less acetate accumulation (Van Nevel and Demeyer, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…The reduction in the proportion of ruminal acetate 12 h after supplementation and higher butyrate concentrations by ENS is in line with results from trials of mixed cultures of rumen microbes incubated with nitrate and nitro-compounds (Zhou et al, 2012; Mamvura et al, 2014; Anderson et al, 2016). It may be a compensatory route for the dispensing of reducing equivalents during the inhibition of rumen methanogenesis, shifting electron transfer mainly to more reduced fatty acids such as propionate and butyrate, as this subsequently results in less acetate accumulation (Van Nevel and Demeyer, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, D. detoxificans gains energy by oxidizing nitrogenous compounds such as nitroethane, 2-nitroalcohol and 3-nitro-1-propionate, using trimethylamine from choline metabolism as electron acceptor 38 . These nitrogenous compounds can be accumulated in forages, in particular legumes such as the alfalfa used in the basal diet in the present study and be made available within the rumen 39 . The N compounds mentioned are known to act as methanogen inhibitors 40 , and thus may have contributed to the CH 4 inhibition observed in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Ruminal conditions that control the favorability of NO -2 reduction may determine the occurrence of the H 2 sink mechanism and the methanogenic inhibition by NO -2 mechanism. A mixed culture in vitro experiment by Anderson et al (2016) indicated a decreased acetate to propionate ratio and an increased headspace p H 2 in response to increased NO -3 supplementation, whereas these changes were impaired when the mixed culture was also inoculated with Denitrobacterium detoxificans, despite a more pronounced decrease of headspace CH 4 partial pressure. This inoculation may have stimulated the reduction of NO -2 and alleviated methanogenic inhibition and H 2 accumulation, and next affected the production of the different VFA.…”
Section: Hydrogen As a Controller Of Fermentationmentioning
confidence: 99%